A Little Death Around the Eyes: Heroin, kulturindustri og Pete(r) Dohertys autofiktioner - Holst Kjær, Sarah (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2009)
This article discusses the relationship between pre-romantic Anglo-Saxon literature, iconology in late modern music industry, artistry performance and heroin abuse in Pete(r) Doherty's musical universe. Through the concept of 'autofiction' which include internet media, self-performativity, intertextuality with previous art-production in literature and music, autobiography and body, this article investigates how Doherty builds his legacy and iconology by positioning himself in a recognizable script of culturally unaccepted libertine masculinity. Still, this script is partly transgressed by installing pre-romantic notions of duality between the 'lost boy' and 'found boy'. The male figures in Doherty's texts speaks from below, and parallel to, a patriarchal hierarchy, which is why his lyrics are interpreted as a way to debate norms and ideals in a bourgeoisie society.